2017
DOI: 10.26681/jote.2017.010102
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an Evidence-Based, Data Driven-Model Fieldwork Experience for Occupational Therapy Students

Abstract: Over the past decade, there has been an increased emphasis on evidence-based practice (EBP) and the use of outcome measurement in clinical practice, however, the implementation of evidence into practice remains challenging and irregular. During fieldwork, students often experience a disconnect between the emphasis on EBP in the classroom and lack of use in the clinic. Recognizing the need to develop high-quality, evidencebased and data-driven models of practice for student training, we partnered with local fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…This study is described in detail in a separate manuscript (Carroll et al, 2017). Findings showed that students had significant improvements in both their knowledge about using evidence and data in practice (p < .05), and in their skills in using DDDM in practice (p < .05).…”
Section: Measuring Outcomes Of Premo ©mentioning
confidence: 89%
See 4 more Smart Citations
“…This study is described in detail in a separate manuscript (Carroll et al, 2017). Findings showed that students had significant improvements in both their knowledge about using evidence and data in practice (p < .05), and in their skills in using DDDM in practice (p < .05).…”
Section: Measuring Outcomes Of Premo ©mentioning
confidence: 89%
“…Faculty have active involvement in promoting EBP in traditional and emerging practice settings as well as opportunities to participate in scholarly inquiry projects at the PrEMO © sites. Fieldwork educators recognize the value PrEMO © offers for furthering their own professional development as they become more skillful and systematic with EBP (Carroll et al, 2017). Fieldwork educators also find the DDDM process strengthens their communication with stakeholders about the occupational therapy process (Carroll et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations